FORCED VIBRATIONS OF CYLINDRICAL BODIES - dots. Nematov Baxron; dots. B. T. Bisenova; Nematova Mohinur (Modern American Journals, 2025)
The article considers forced vibrations of cylindrical layers in interaction with elastic systems. The internal pressures of the cylindrical layer and the elastic system, the continuous vibrational motion under the influence of harmonic, longitudinal P waves are studied. The changes in the ring stresses and absorptions generated in the cylindrical layer and the mechanical system with respect to the wave number are studied.